2018
DOI: 10.5935/1518-0557.20180011
|View full text |Cite
|
Sign up to set email alerts
|

ANDRO-IVF: a novel protocol for poor responders to IVF controlled ovarian stimulation

Abstract: ObjectiveThis study aimed to assess a novel protocol designed to improve poor ovarian response through intra-ovarian androgenization. The endpoints were: number of oocytes and mature oocytes retrieved, fertilization, cancellation and pregnancy rates.MethodsThis prospective crossover study enrolled poor responders from previous ovarian stimulation cycles submitted to a novel protocol called ANDRO-IVF. The protocol included pretreatment with transdermal AndroGel(r) (Besins) 25 mg, oral letrozole 2.5 mg and subcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 22 publications
1
11
0
1
Order By: Relevance
“…A significant improvement in the number of oocytes retrieved and clinical pregnancy rates was reported in a study that used a combination therapy of DHEA for 12 weeks, transdermal testosterone for 4 weeks and growth hormone later in the luteal phase (Haydardedeoglu et al 2015). Additionally, in another treatment strategy, called ANDRO-IVF, combining pre-treatment with transdermal testosterone, letrozole and hCG, it was reported that POR patients exhibited a significant increase in the number of oocytes retrieved and fertilization rates (Bercaire et al 2018). However, it is noteworthy that neither study had a placebo control.…”
Section: Androgen or Androgen-modulating Agent Combination Therapiesmentioning
confidence: 91%
“…A significant improvement in the number of oocytes retrieved and clinical pregnancy rates was reported in a study that used a combination therapy of DHEA for 12 weeks, transdermal testosterone for 4 weeks and growth hormone later in the luteal phase (Haydardedeoglu et al 2015). Additionally, in another treatment strategy, called ANDRO-IVF, combining pre-treatment with transdermal testosterone, letrozole and hCG, it was reported that POR patients exhibited a significant increase in the number of oocytes retrieved and fertilization rates (Bercaire et al 2018). However, it is noteworthy that neither study had a placebo control.…”
Section: Androgen or Androgen-modulating Agent Combination Therapiesmentioning
confidence: 91%
“…Through the categorized analysis of the 27 articles that composed the final sample, we found that all were published between 2003 and 2019. Of these, 4 were cross-sectional studies ( Pasqualotto et al ., 2003 ; Esteves & Glina, 2005 ; Cota et al ., 2012 ; Souza et al ., 2017 ), 12 were cohort studies ( Pinheiro et al ., 2003 ; Borges et al ., 2003 ; Glina et al ., 2005 ; Pasqualotto et al ., 2005 ; Romão et al ., 2010 ; Semião-Francisco et al ., 2010 ; Cota et al ., 2012 ; Borges et al ., 2013 ; Coelho Neto et al ., 2015 ; Maia-Filho et al ., 2015 ; Scheffer et al ., 2017 ; Bercaire et al ., 2018 ); 6 were case-control studies ( Setti et al ., 2011 ; Pasqualotto et al ., 2012 ; Cavagna et al ., 2012 ; Picinato et al ., 2014 ; Donabela et al ., 2015 ; Costa et al ., 2016 ); 3 were case reports ( Valle et al ., 2012 ; Taitson et al ., 2012 ; Borges et al ., 2016 ) and 2 were randomized controlled trials ( Geber & Sampaio, 2013 ; Nastri et al ., 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…They reported a significantly lower cancellation rate, a higher number of oocytes and metaphase II oocytes, a higher fertilization rate and a higher number of embryos per patient and concluded that the protocol seemed to improve clinical outcomes. However, the small sample size, the use of higher daily gonadotropin doses and longer duration of OS, as well-including failed cycles only as controls (with a known tendency of regression toward the mean) limit firm conclusions, and as the authors state, further RCTs are needed (67).…”
Section: Clinical Trials Investigating Androgen Priming By Use Of Hcgmentioning
confidence: 98%
“…Bercaire and coworkers ( 67 ) investigated an “ANDRO-IVF protocol” including a 24-days pretreatment in poor responder patients ( n = 13) who had undergone a failed IVF cycle, which was later used as the control. From CD one transdermal AndroGel(r) ( 67 ) 25 mg every other day, oral letrozole 2.5 mg daily, and hCG 2500 IU subcutaneously twice a week were administered. Cycle control was performed with estradiol valerate from CD three to CD 15 followed by micronized progesterone from CD 15 to CD 24, followed by a new menstrual cycle, in which high dose OS and IVF took place.…”
Section: Clinical Trials Investigating Androgen Priming By Use Of Hcgmentioning
confidence: 99%